Field study 3 : technology in the learning environment activity sheets - Reganit, Arnulfo Aaron R.; Gavino, Renato L. (Quezon City, Philippines : C & E Publishing Inc., 2008)
Field student is intended to provide students with practical learning experiences through observation, verification, reflection on, and actual experience of the different components of the dynamic teaching-learning, processes in actual school settings.
Activity sheet 1- The school's learning resources -- Activity sheet 2- The school's learning resources -- Activity sheet 3- Bulletin board displays -- Activity sheet 4- Bulletin board displays -- Activity sheet 5- Utilization of teaching aids -- Activity sheet 6- Utilization of teaching aids -- Activity sheet 7- A teaching aids bank -- Activity sheet 8- A teaching aids bank -- Activity sheet 9- Slide presentation -- Activity sheet 10- Slide presentation -- Activity sheet 11- On-line learning -- Activity sheet 12- On-line learning
Keywords: EDUCATION -- PHILIPPINES